The Presence of Television Media in Disaster Reporting to Increase the Community’s Disaster Literacy Skills - Effiati Juliana Hasibuan; Dedi Sahputra; Mazdalifah Mazdalifah (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
Television media, on the one side, has an influence on the audience, but in reporting disasters, it is not uncommon to exploit disaster victims. On the other side, television media has the potential to make a positive contribution to disaster reporting. The purpose of this study is  to determine the presence of television media in news to improve the disaster literacy skills of the community. In this study, the author uses a type of library research with descriptive analysis. Descriptive analysis method provides clear, objective, systematic, analytical and critical descriptions and information regarding the presence of television media in disaster reporting to improve the community’s disaster literacy skills. This research found that the role of television media in reporting disasters can improve people's disaster literacy skills. The presence of television media has been going well enough in reporting disasters, but it still needs to change the concept or packaging of news to avoid the impression of "dramatization" to build community empathy so that they are willing to be actively involved to reduce the risk of disaster in an applicative manner. A good and deep understanding will be obtained by the public from the media. Thus,  the public will not only get information from communicators (resource persons) about disasters at a cognitive level but also will increase the affective and conative aspects so that they have their own awareness in managing disaster risks as well as possible.  This paper explained there are three stages of disaster literacy that can be built by television such as cognitive aspect, affective aspect and conative aspect in disaster reporting that can reduce the risk of disaster. The stages are: (1) when the news is carried out by television media before a disaster occurs, (2) stage of reporting during disasters and (3) stage of television media coverage after disasters.